Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Circulation and exchanges at high-latitude ocean margins : dynamical models and observations from instrumented seals - Zhou, Qin; Eltoft, Torbjørn (UiT The Arctic University of Norway, 2013)
Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf cavity after being brought on-shore by wind-driven surface Ekman transport, and being spread below the depth of the ice base within a regime of coastal downwelling. The results also suggest a complex picture of water mass exchange processes along the coast of Eastern Weddell Sea, in which mesoscale eddies play a central role. Finally, the data collected by the seals are employed to evaluate the performance of a global coupled ocean-ice model incorporated with a parametrization of wave-induced mixing in simulating the upper ocean properties in the Southern Ocean. The results suggest that wave-induced mixing is important to modify the upper ocean properties. Since coastal water properties in the Eastern Weddell Sea are mainly determined by the onshore Ekman transport of surface waters, the wave-induced mixing also plays a role in preconditioning the coastal water masses in this region. I dette arbeidet er sirkulasjon og blandingsmekanismer i havområder på høge breddegrader undersøkt ved bruk av analytiske modeller, numeriske simuleringer og havobservasjoner. På den nordlige halvkulen er det undersøkt hvordan transport av Atlanterhavsvann etablerer seg som en topografisk styrt strøm langs kontinentalsokkelskråningen. En forenklet analytisk modell basert på geostrofisk balanse kan forklare hvordan varmetap i vannet som strømmer langs en skrånende bunn fører til en baroklin strøm på tvers av skråningen som igjen blir transformert til en barotrop strøm langs den skrånende bunnen. Denne transportendringen kan man beregne fra hydrografiske data. En slik beregnet transportendring over kontinentalsokkelskråningen vest for Skotland stemmer godt overens med observert transportendring i denne regionen. Resultatene understreker at geostrofi kan bli brukt til å diagnostisere topografisk styrte strømmer, noe som gjør teorien spesielt egnet for å studere oseanografi på høge breddegrader der topografisk styring av strømmene er mest tydelig. I det østlige Weddellhavet, i den atlantiske sektoren av Antarktis, har prosessene som styrer vannmasseutvekslingen på tvers av kontinentalsokkelskråningen blitt undersøkt ved å ta i bruk mer enn 11.000 havprofiler som er blitt samlet inn av seler i denne regionen fra februar til november 2008. Selene var utsyrt med temperatur-, salt- og dybde-loggere. Den foreslåtte mekanismen at vind-drevet nedstrømning er ansvarlig for oppsamling av antarktisk overflatevann nær isbremmen og for dens videre spredning under den flytende isbremmen langs kysten av den østlige Weddellhavet, er testet ved hjelp av en kombinasjon av detaljerte dataanalyser av observasjonene som ble samlet inn av selene, en analytisk modell og numeriske simuleringer. Resultatene viser at det antarktiske overflatevannet entrer hulområdet under isbremmen etter at det er blitt fraktet mot isbremmen som Ekman-transport i overflaten. Spredningen på undersiden av den flytende isbremmen kan forklares ved hjelp av samme mekanisme som nedstrømning langs en kyst. Resultatene tyder også på at vannmasseutvekslingen langs kysten av det østlige Weddellhavet er sammensatt av flere prosesser der virvler av mesoskala størrelse spiller en sentral rolle. Til slutt er dataene som ble samlet inn av selene blitt brukt til å evaluere en global hav-is-modell som har innebygget en parameterisering av bølgedrevet blanding i Sørhavet. Resultatene indikerer at bølgedrevet blanding er viktig for å modifisere hva de øvre vannmassene i Sørhavet er sammensatt av. Siden sammensetningen i kystvann i det østlige Weddellhavet er hovedsakelig bestemt av Ekmantransport inn mot kysten, vil bølgedrevet blanding også spille en rolle når det gjelder å danne kystvannmassene i denne regionen.
Keywords: Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Seler brukt som "forskningsassistenter" for å utforske polhavene - Kovacs, Kit M (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Isolation and partial characterization of a parapoxvirus isolated from a skin lesion of a Weddell seal - Tryland, M.; Klein, J.; Nordøy, E.S.; Blix, A.S. (Virus Research, 2005)
A solitary skin lesion was found on the neck of a Weddell seal (Leptonychotes weddellii), chemically immobilized in Queen Maud Land (70°09′S, 05°22′E) Antarctica 2001. The lesion was elevated and 3cm in diameter, consisting of partly fresh and partly necrotic tissue, and proliferative papilloma-like structures were seen. Electron microscopy on a biopsy from the lesion revealed typical parapoxvirus particles. Polymerase chain reaction (PCR; B2L gene) generated amplicons of approximately 594 base pairs, comparable to Orf-virus, the prototype parapoxvirus. A comparison of these B2L PCR amplicon DNA sequences with corresponding sequences from other parapoxviruses, showed that the Weddell seal virus resembled isolates from grey seal (Halichoerus grypus) and harbour seal (Phoca vitulina) more than parapoxvirus from red deer (Cervus elaphus), sheep, cattle and Japanese serows (Capricornis crispus). It is thus concluded that the Weddell seal parapoxvirus belong to the tentative seal parapoxvirus species. Since parapox and orthopoxviruses may cause similar clinical diseases, we suggest that the term sealpox should be restricted to the clinical disease, whereas seal parapoxvirus should be used when caused by a parapoxvirus, rather than the general term “sealpox virus”. This is the first verified case of parapoxvirus infection in a Weddell seal, and also the first report of any such infections in the Antarctic.
Keywords: Dronning Maud Land; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi; pinnipedier; seler; virologi

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Pinniped and seabird research at Bouvetøya, 2000/01 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; fugler; pelsseler; pinnipedier; seler; zoologi

Pinniped research at Bouvetøya, 2001/02 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Bouvetøya pinniped monitoring programme: December 1998 - February 1999: final contract report for the Norwegian Polar Institute - Kirkman, Stephen; Bester, Marthán ([Universty of Pretoria], 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Studies of seals and seabirds on Bouvetøya 2000/01 - fieldwork and preliminary results - Krafft, Bjørn; Hofmeyr, Greg J G; Keith, Dave; Harck, Bianca I B; Kovacs, Kit M (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; biologi; fugler; ornitologi; seler; zoologi

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi

Counts of southern elephant seals, Mirounga leonina, at Bouvet Island - Kirkman, S. P.; Hofmeyr, G. J. G.; Bester, M. N.; Isaksen, K. (Polar Biology, 2001)
Southern elephant seals were counted and classified into subjective sex-age classes on a weekly basis during expeditions to Bouvet Island in the austral summers of 1996/1997 and 1998/1999. The expeditions coincided with the moulting period of elephant seals aged one year and older. The presence of weaned pups at the principal haulout site, Nyrøysa/Westwindstranda, during the latter expedition, indicates that breeding took place here during 1998. Elephant seal counts from previous expeditions are summarised.
Keywords: Bouvetøya; NARE 1996/97; NARE 1998/99; marin biologi; pinnipedier; seler

Studies of seabirds and seals on Bouvetøya 1998/99 - Isaksen, Kjell; Huyser, Onno; Kirkman, Steve; Wanles, Ross; Wilson, Wendy (2000)
Keywords: Bouvetøya; forskning; fugler; pinnipedier; seler; zoologi

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler